Close Relationship Between Immunological/Inflammatory Markers and Myopenia and Myosteatosis in Patients With Colorectal Cancer: A Propensity Score Matching Analysis. Issue 4 (18th October 2018) - Okugawa, Yoshinaga; Toiyama, Yuji; Yamamoto, Akira; Shigemori, Tsunehiko; Kitamura, Ayame; Ichikawa, Takashi; Ide, Shozo; Kitajima, Takahito; Fujikawa, Hiroyuki; Yasuda, Hiromi; Okita, Yoshiki; Hiro, Junichiro; et al.
Abstract: Background: The systemic inflammatory response (SIR) via host‐tumor interactions has been termed the seventh hallmark of cancer, and several studies demonstrated that SIR might be a pivotal mediator for progression of cancer cachexia. The objective of this study was to clarify the correlation between sarcopenia and SIR in patients with colorectal cancer (CRC). Methods: A total of 308 patients with CRC were enrolled in this study. Preoperative psoas muscle mass index and intramuscular adipose tissue content were evaluated using preoperative computed tomographic images, and the correlation between body composition status and several SIR markers, including C‐reactive protein (CRP), serum albumin level, neutrophil‐lymphocyte ratio, platelet‐lymphocyte ratio, and systemic immune‐inflammation index (SII) was assessed using statistical methods. Results: Whereas preoperative myosteatosis was not correlated with clinicopathological factors except for aging and the presence of lymphovascular invasion, preoperative myopenia was significantly associated with well‐established clinicopathological factors. Furthermore, the presence of myopenia was significantly correlated with elevated CRP, SII, and neutrophil‐platelet score, and decreased lymphocyte‐monocyte ratio, prognostic nutrition index, and serum albumin level. Logistic regression analysis revealed that an elevated CRP concentration was an independent risk factor for the presence of preoperative myopenia (odds ratio [OR] 2.49, 95% CI: 1.31–4.72; P = .005). Furthermore, these findings were validated using propensity score matching analysis (OR 2.35, 95% CI: 1.17–4.75; P = .017). Conclusion: Quantification of preoperative CRP could identify patients at high risk for development of myopenia who will likely require individualized treatment plans, including postoperative nutrition intervention, rehabilitation, and oncological follow‐up in patients with CRC.